(untitled) (Herald of Journalism, 2022)
The author of the article translated from the Arabic alphabet into Cyrillic the first Kazakh satirical magazine published in 1925 and introduced into scientific circulation. Therefore, the history, purpose and mission of «Shanshar» was widely analyzed in the article. The article is analyzed by satirical publica- tions published in the pages of the publication of political, social, literary content. Defective and rational aspects of cartoons constructed in accordance with the content of the journal are determined. The author comes to the conclusion that some historical moments in the Kazakh society were included in the journal «Shanshar». Key words: «Shanshar» magazine, Ak zhol, feuilleton, satire, magazine of humor.